Controllability of dynamic‐algebraic Boolean networks based on a new normalisation approach. Issue 13 (1st September 2017) - Li, Bowen; Lou, Jungang; Shi, Wenping; Liu, Yang; Alsaedi, Ahmed; Alsaadi, Fuad
Abstract : In this study, the controllability of dynamic‐algebraic Boolean control networks is investigated based on a new normalisation approach. Some lower dimensional controllability matrices are defined, and new necessary and sufficient conditions for the controllability are presented as well. An example is given to illustrate the efficiency of the proposed results.